1994
DOI: 10.1143/jjap.33.230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Relaxation Process of Compressive and Tensile Strains in InGaAs Lattice-Mismatched Layers on InP Substrates

Abstract: This paper investigates the difference in crystal quality between strained-layer multiple quantum wells with compressive (+0.5%) and tensile strains (-0.5 %). For the compressive strain, the photoluminescence intensity decreased and the length of fringe bending increased from 250 Å to 500 Å when the number of periods increased from 5 to 15. The amount of fringe bending increased when the InP thickness decreased, especially when the strain was compressive. We also investigated the relaxation process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In the typical case, as reported in InGaAs/InP [20,21] and PrBa 2 Cu3O 7−x /SrTiO 3 [22], the dislocation density decreases with increase film thickness. This trend is opposite in the VO 2 thin films on TiO 2 (001) as shown in Fig.…”
Section: Figures 4(c) and 4(d)supporting
confidence: 55%
See 2 more Smart Citations
“…In the typical case, as reported in InGaAs/InP [20,21] and PrBa 2 Cu3O 7−x /SrTiO 3 [22], the dislocation density decreases with increase film thickness. This trend is opposite in the VO 2 thin films on TiO 2 (001) as shown in Fig.…”
Section: Figures 4(c) and 4(d)supporting
confidence: 55%
“…We found that domain size decreased with increasing film thickness and that the domain boundary contained cracks and dislocations. The dislocation density increased with increasing film thickness, as the domain size decreased, showing a different tendency from that in other systems [20][21][22]. These dislocations formed from the release of strain energy caused by a phase transformation from tetragonal to monoclinic against the pinning tetragonal layer near the interface.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Strain relaxation by plastic deformation occurs by threading dislocations, dislocations along the substrate-film interface, or by twinning [1][2][3][4][5][6][7][8][9]. Relaxation by cracking is commonly observed in highly strained heterostructures [8][9][10][11][12][13][14][15][16]. The relaxation of purely elastic stresses leads to the development of surface undulation [8,9,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, some additional mechanism that is dependent on surface-orientation likely exists that alters or in relation to . Tensile strain is predicted to have a higher barrier to dislocation nucleation, yet lower strain accumulation [81], [82], consistent with the early strain relaxation that occurs with VW growth.…”
Section: Entangled Photon Emission Detectionmentioning
confidence: 53%